2020
DOI: 10.3390/biom10020174
|View full text |Cite
|
Sign up to set email alerts
|

The Guanidine Pseudoalkaloids 10-Methoxy-Leonurine and Leonurine Act as Competitive Inhibitors of Tyrosinase

Abstract: Tyrosinase plays a key role in the production of melanin. A variety of industrial fields have shown interest in the development of tyrosinase inhibitors from plants. In this study, compounds 1–5 derived from Leonurus japonicas were evaluated to determine their ability to inhibit tyrosinase. Of these, 10-methoxy-leonurine (1) and leonurine (2) exhibited IC50 values of 7.4 ± 0.4 and 12.4 ± 0.8 μM, respectively, and acted as competitive inhibitors of tyrosinase, with Ki values in the micromolar range. In silico m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
3
3
0
Order By: Relevance
“…On the other hand, the IC50 value described is 14.64 µM and the K I value = 67.60 µM [ 10 ], but in the case of a competitive inhibitor, it can be shown that IC50 > K I , specifically IC50 = (n+1)K I , where n is the ratio of substrate concentration to Km [ 36 ]. This relationship between IC50 and K I is well established in the data shown in Tables 1 and 2 in [ 37 ] and in Table 1 in [ 38 ]. The relationship of rates of consumption of M, O 2 and formation of DC described in Table S5 of the Supporting Information [ 10 ] shows in the monophenolase activity the equality of rates of consumption of O 2 and consumption of M, however the DC formation rate is not comparative; this aspect confirms the validity of the measure measuring O 2 consumption that was described previously [ 9 ].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…On the other hand, the IC50 value described is 14.64 µM and the K I value = 67.60 µM [ 10 ], but in the case of a competitive inhibitor, it can be shown that IC50 > K I , specifically IC50 = (n+1)K I , where n is the ratio of substrate concentration to Km [ 36 ]. This relationship between IC50 and K I is well established in the data shown in Tables 1 and 2 in [ 37 ] and in Table 1 in [ 38 ]. The relationship of rates of consumption of M, O 2 and formation of DC described in Table S5 of the Supporting Information [ 10 ] shows in the monophenolase activity the equality of rates of consumption of O 2 and consumption of M, however the DC formation rate is not comparative; this aspect confirms the validity of the measure measuring O 2 consumption that was described previously [ 9 ].…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, the IC50 value described is 14.64 µM and the K I value = 67.60 µM [ 10 ], but in the case of a competitive inhibitor, it can be shown that IC50 > K I , specifically IC50 = (n+1)K I , where n is the ratio of substrate concentration to Km [ 36 ]. This relationship between IC50 and K I is well established in the data shown in Tables 1 and 2 in [ 37 ] and in Table 1 in [ 38 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Different classes of secondary metabolites have been identified in L. cardiaca . In particular, flavonoids (e.g., flavonols such as quercetin and rutin, flavones such as genkwanin and apigenin, and their relative glycosides) [ 7 ], phenylethanoid glycosides (e.g., verbascoside and lavandulifolioside) [ 8 ], iridoids (e.g., harpagide), labdane diterpenes (e.g., forskolin) [ 9 , 10 ], p -hydroxycinnamic acid derivatives (e.g., ferulic, chlorogenic and caffeic acids) [ 11 ], guanidine pseudoalkaloids (e.g., leonurine) [ 12 ], and betains (e.g., stachydrine, and turicin) [ 10 ]. The essential oil obtained from the leaves was reported to contain β -caryophyllene and α -humulene as the major compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of caffeine to Tyr promoted a conformational change of a loop so as to fit in Tyr’s active site. Two pseudoalkaloids isolated from the herb Leonurus japonicas (Yi Mu Cao) [ 180 ] (10-methoxy-leonurine and leonurine) interacted with Tyr’s active site, according to docking simulations. 10-methoxy-leonurine was totally fitted into Tyr’s active site through hydrophobic bonds between the aromatic ring and the amino acids, while the ketonic ester moiety interacted with His244 at a distance of 3.5 Å.…”
Section: Enzymes Related To Early Skin-agingmentioning
confidence: 99%